EFFECTIVENESS OF INTRAUTERINE CONTRACEPTION DEVICE IN MULTIPAROUS WOMEN - Akram, S; KHALID, M; MUSTAFA, S; SAIF, M; SAQIB, AB; YOUSAF, S (Biological and Clinical Sciences Research Journal, 2024)
Intrauterine devices (IUDs) serve as long-term contraceptive methods by being inserted into the uterine cavity to prevent fertilization. Copper-based IUDs and levonorgestrel-releasing IUDs are among the most commonly used types, offering an effective alternative to hormonal contraception methods like the "morning-after" pill. Objective: The study aims to assess the effectiveness of intrauterine contraceptive devices in multiparous women during the early postpartum period. Methods: This descriptive case series was conducted at the Department of Obstetrics and Gynecology, Shalamar Hospital, Lahore. The study spanned six months, from 26-08-2019 to 25-02-2020. A total of 109 multiparous women were included, who received IUD insertion via the vaginal route within 48 hours post-delivery. Follow-up was conducted in the outpatient department (OPD) for six months, with subsequent confirmation of IUD presence. Complications were evaluated, and effectiveness was assessed. Results: The average age of participants was 30.0±4.6 years, with an average gestation period of 30.0±4.6 weeks, BMI of 25.4±2.8 kg/m2, and parity of 3.0±0.9. The majority of subjects were enrolled (41.3%), followed by secondary (33%), primary (19.3%), and illiterate (6.4%). Intrauterine contraceptive effectiveness was monitored in 69 women (63.3%). Conclusion: The study concludes a high effectiveness rate (63.3%) of IUDs in multiparous women. Copper T emerges as the most effective, safe, long-acting, and commonly used contraception method.